276 Wolff–Parkinson–White syndrome was associated with reduced myocardial work. (8th December 2021) - Ciriello, Giovanni Domenico; Borrelli, Nunzia; Di Salvo, Giovanni; Sabatino, Jolanda; Bucciarelli, Valentina; Avesani, Martina; Grimaldi, Nicola; Barracano, Rosaria; Fusco, Flavia; Merola, Assunta; Correra, Anna; Romeo, Emanuele; et al.
Abstract: Aims: Paediatric patients with a diagnosis of Wolff–Parkinson–White (WPW) Syndrome may develop a reduction of local myocardial deformation because of accessory pathway-related electrical dyssynchrony, which may lead to an impairment of left ventricular systolic function. The presence of ventricular dysfunction may be an indication for these patients to undergo radiofrequency catheter ablation (RFCA), even if asymptomatic. However, myocardial abnormalities are sometimes subtle and cannot be detected by standard echocardiographic evaluation. The purpose of this study was to assess the diagnostic value of non-invasive myocardial work in predicting subtle myocardial abnormalities in paediatric patients with WPW Syndrome. Methods and results: Forty-four paediatric patients (age 8.2 ± 4.3 years) were included in this study: 12 cases with manifest WPW Syndrome and 32 age-, sex-, and arterial pressure-matched controls (CTR). Left ventricular ejection fraction (LVEF) and global longitudinal strain (GLS) were evaluated. Global myocardial work index (MWI) was measured as the area of the LV pressure-strain loops. From MWI, global constructive work (MCW), wasted work (MWW), and work efficiency (MWE) were estimated. Despite normal LV systolic function by standard echocardiographic parameters, paediatric patients with WPW Syndrome had lower MWI (1233.5 ± 281.6 mmHg% in WPW vs. 1624.0 ± 305.8 mmHg% in CTR, P = 0.0004), MCW (1833.4 ± 257.9 mmHg% in WPW vs. 2069.0 ± 319.9 mmHg% in CTR, P = 0.03), MWW (187.6 ± 117.7 mmHg% in WPW vs. 90.9 ± 58.9 mmHg% in CTR, P = 0.0008), and GWE (90.5 ± 4.8% in WPW vs. 95.2 ± 2.2% in CTR, P = 0.00006). There were no significant differences in GLS and LVEF between patients with WPW Syndrome and controls. Conclusions: WPW Syndrome was found to be associated with a significant reduction of myocardial work indices in the paediatric population. The assessment of MWI may represent a sensitive measure to identify a subtle myocardial dysfunction in an early stage, even when LVEF and GLS are normal. It might be considered a further diagnostic parameter for referring little patients to RFCA.